IL-21 promotes the development of a CD73-positive Vγ9Vδ2 T cell regulatory population. (2nd January 2018) - Barjon, Clément; Michaud, Henri-Alexandre; Fages, Angeline; Dejou, Cécile; Zampieri, Alexandre; They, Laetitia; Gennetier, Aurélie; Sanchez, Françoise; Gros, Laurent; Eliaou, Jean-François; Bonnefoy, Nathalie; Lafont, Virginie
ABSTRACT: Vγ9Vδ2 T cells contribute to the immune response against many tumor types through their direct cytotoxic activity and capacity to regulate the biological functions of other immune cells, such as dendritic cells and IFN-γ-producing CD8 + T cells. However, their presence in the tumor microenvironment has also been associated with poor prognosis in breast, colon and pancreatic cancers. Additionally, recent studies demonstrated that cytokines can confer some plasticity to Vγ9Vδ2 T cells and promote their differentiation into cells with regulatory functions. Here, we demonstrated that activation of Vγ9Vδ2 T cells isolated from healthy donors and cultured in the presence of IL-21 favors the emergence of a subpopulation of Vγ9Vδ2 T cells that express the ectonucleotidase CD73 and inhibits T cell proliferation in a CD73/adenosine-dependent manner. This subpopulation produces IL-10 and IL-8 and displays lower effector functions and cytotoxic activity than CD73-negative Vγ9Vδ2 T cells. We also showed, in a syngeneic mouse tumor model, the existence of a tumor-infiltrating γδ T cell subpopulation that produces IL-10 and strongly expresses CD73. Moreover, maturation, IL-12 production and induction of antigen-specific T cell proliferation are impaired in DC co-cultured with IL-21-amplified Vγ9Vδ2 T cells. Altogether, these data indicate that IL-21 promotes Vγ9Vδ2 T cell regulatory functions by favoring the development of an immunosuppressive CD73 + subpopulation. Thus, when present in the tumor microenvironment, IL-21 might negatively impact γδ T cell anti-tumor functions.